STUDI KELAYAKAN DAN ANALISIS RISIKO PENERAPAN SISTEM PENYEDIAAN AIR SIAP MINUM PDAM KOTA SURABAYA DI APARTEMEN - Annas Taufan; Adhi Yuniarto (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
The city of Surabaya as the center of government and business in East Java has made the city of Surabaya experience rapid property growth in all types including apartment growth. The high growth of apartment units in Surabaya, whether they have been built, are being built, or are planned for construction will be in line with the increasing population growth in the city of Surabaya. This will be accompanied by an increase in the need for drinking/ potable water in the apartment itself. The purchase price of PDAM water specifically for apartments, which is more expensive than the landed house rate, also burdens the apartment residents. Therefore, we need initiatives and efforts to meet the demand for ready-to-drink water for apartments. This study will analyze the technical aspect, financial aspect, and risk analysis of the application of a ready-to-drink water supply system in an apartment so that it can be used as reference material or material for further academic studies. Based on the analysis that has been carried out, the application of a ready-to-drink water supply system in the apartment is declared technically and financially feasible. Risk mitigation related to the application of a ready-to-drink water supply system in apartments is carried out by allocating risk to parties who are relatively able to manage it or because they have the lowest cost to absorb this risk.